Neurogenesis and learning: acquisition and asymptotic performance predict how many new cells survive in the hippocampus. - Dalla, Christina; Bangasser, Debra A; Edgecomb, Carol; Shors, Tracey J (Neurobiol Learn Mem, 2007)
Previous research has shown that some associative learning tasks prevent the death of new neurons in the adult hippocampus. However, it is unclear whether it is mere exposure to the training stimuli that rescues neurons or whether successful learning of the task is required for enhanced neuronal survival. If learning is the important variable, then animals that learn better given the same amount of training should retain more of the new cells after learning than animals that do not learn as well. Here, we examined the effects of training versus learning on cell survival in the adult hippocampus. Animals were injected with BrdU to label a population of cells and trained one week later on one of two trace conditioning tasks, one of which depends on the hippocampus and one that does not. Increases in cell number occurred only in animals that acquired the learned response, irrespective of the task. There were significant correlations between acquisition and cell number, as well as between asymptotic performance and cell number. These data support the idea that learning and not simply training increases the survival of the new cells in the hippocampus.
Keywords: Animals; Association Learning; Cell Differentiation; Cell Survival; Conditioning, Classical; Hippocampus; Male; Neurons; Rats; Rats, Sprague-Dawley; Stem Cells